Analisis Dampak Pembangunan Jalan Produksi Perkebunan Terhadap Peningkatan Perekonomian Masyarakat Desa - Ulfa E. R. Ollong; Maryam Sangadji; Muspida Muspida (Univiversitas Dr. Djar Wattiheluw, 2024)
One effort to develop the agricultural sector is by enhancing adequate agricultural infrastructure support, including through the development of Production Roads. This research aims to determine the impact of Production Road development on time efficiency, distribution, and community income in Latu Village. This is a comparative study that compares the perceptions of paired respondent samples using the Sign Test analysis method. The results of this study show that, partially, time efficiency and community income have a negative rank value of 0, and positive rank value of 24, indicating a difference and significant impact before and after the Production Road development. However, farmer community distribution has a negative rank value of 18, while the positive rank has a value of 0, meaning there is no significant impact on distribution before and after the Production Road is built in Latu Village, Amalatu District, West Seram Regency.